The signs of differentiation of chondrocytes in the formation of early cartilage lesions in the elderly - Elena Vasil'evna Chetina; Elena Vasilyevna Chetina (Научно-практическая ревматология, 2011)
Objective. To study the relationship between the activity of collagen type II cleavage and the pattern of expression of the genes responsible for chondrocyte differentiation in the areas of intact cartilaginous tissue and in those of early focal cartilage lesions similar to those observed in elderly people with osteoarthrosis (OA). Material and methods. The distal femoral articular surface of the knee joint that articulated with the patella and had focal lesions was examined in the elderly. Collagen type II cleavage was estimated by enzyme immunoassay. Gene expression was determined with reverse-transcription polymerase chain reaction. Results. The activity of collagen type II cleavage was shown to be increased in the area of age-related OA-like cartilage lesions. This was accompanied by the high expression of collagenases of metalloproteinases (MMP) 1, 14 (MT1-MMP), aggrecanases - desintegrin and MMP with thrombospondin type 1 motif (ADAMTS) 5, the cytokines of interleukins (IL) 1α/β and tumor necrosis factor-α (TNF-α), as well as the genes associated with chondrocyte hypertrophy of type X collagen (C0L10A1), MMP 13 and 9, Indian hedgehog (Ihh) and cas-pase 3 in the immediate vicinity of a lesion area. At the same time, there was a high expression of growth factors associated with the proliferation phase of chondrocytes, namely: parathyroid hormone-related peptide (PTHrP), fibroblast growth factor-2 (FGF-2), transforming growth factor β1/2 (TGF-β1/2), as well as macromolecules of matrix of type II collagen (C0L2A1) and aggrecan in both the areas adjacent to the lesions and at a considerable distance from their center. However, these areas showed no higher collagen cleavage activity. Nether higher collagen cleavage, nor excess expression of the genes examined were observed in the absolutely intact cartilage areas. Conclusion. Our studies have indicated that the area of very early age-related OA-like focal cartilage lesions exhibits enhanced type II collagen cleavage that is attended by the expression of the genes associated with chondrocyte differentiation in the embryonic growth plate.